Microwave assisted synthesis and characterization of Al2O3. (2022) - Rajagopalan, Kandeeban; Revathi, K.; Revathi, B.; Vishalee, S.; Manojkumar, K.; Mujasam Batoo, Khalid; Saminathan, K.; Kathireswari, P.
Abstract: Microwave radiations produce heat on any materials that contains mobile electric charges by acting as high frequency electric field. Alumina Nanoparticles are the future of aluminium used platforms. Effectiveness, compact size, better conductivity and many more facilities can be attained by alumina nanoparticles. In this work, a facile, cost effective microwave method to prepare Aluminium Oxide Nanoparticles is used for synthesis with variations. Two types of aluminium precursor were used. Various parameters were changed to study the size and shape of the resultant particles. FT-IR was taken to confirm the presence of the compounds. The prepared nano particles was characterized by XRD the shape and size of the sample was analyzed by Scanning Electron Microscopy. Precursors and Microwave power were the key factors of the size of nanoparticles. This work will continue in electrochemistry oriented applications.